Nutritional Evaluation of Some Fortified Traditional Weaning Meals from Oriade Local Government Area of Osun State, Nigeria - Bamisaye, F.A.; Ajani, Emmanuel Oladipo; Nurain, I.O.; Minari, J.B. (International Journal of Applied Sciences and Biotechnology, 2014)
Nutritional status of traditional weaning meals used in Oriade Local Government Area of Osun State Nigeria, were evaluated. Five different fortified weaning meals were labeled as Red beans based diet (RBD), White beans based diet (WBD), Groundnut based diet (GND), Soya beans based diet (SBD) and Sorghum based diet (SGD) were used to feed five groups of young rats of three weeks old. The initial weights of rats were noted and thereafter maintained on their respective diet for twelve weeks. The final body weights of the rats were also noted after the twelve weeks of experiment. The rats were then sacrificed and their liver, heart and kidney weights were noted and compared. The results revealed that soya beans based diet produced the best growth compared with other formulas and control. However, this study concluded by advising nursing mothers to complement these weaning formulas with one another to wean their babies since, if prepared hygienically may improve nutritional status of their babies. DOI: http://dx.doi.org/10.3126/ijasbt.v2i3.10955 Int J Appl Sci Biotechnol, Vol. 2(3): 359-363